2001
DOI: 10.1023/a:1007891716593
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of emotion focused therapy for adult survivors of child abuse: A preliminary study

Abstract: This study examined the effectiveness of Emotion Focused Therapy with 32 adult survivors (EFT-AS) of childhood abuse (emotional, physical, and sexual). EFT-AS is a 20-week individual psychotherapy based on current emotion theory and experiential therapy theory and research. The study employed a quasi-experimental design in which participants, who met screening criteria, were assigned to therapy or a variably delayed therapy condition. Clients receiving EFT-AS achieved significant improvements in multiple domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 26 publications
3
97
1
2
Order By: Relevance
“…This finding challenges the notion that early abuse may impair the development of the therapeutic relationship, as suggested by previous literature linking extreme maltreatment to poorer alliance quality in adolescents (Elz, Shirk, & Sarlin, 1994 (Paivio & Nieuwenhuis, 2001;Paivio & Patterson, 1999). In fact, these data expand this premise by including both patient and therapist alliance ratings and by demonstrating no significant differences when comparing the abuse group with a non-abused clinical control group.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…This finding challenges the notion that early abuse may impair the development of the therapeutic relationship, as suggested by previous literature linking extreme maltreatment to poorer alliance quality in adolescents (Elz, Shirk, & Sarlin, 1994 (Paivio & Nieuwenhuis, 2001;Paivio & Patterson, 1999). In fact, these data expand this premise by including both patient and therapist alliance ratings and by demonstrating no significant differences when comparing the abuse group with a non-abused clinical control group.…”
Section: Discussioncontrasting
confidence: 75%
“…Interpersonal functioning seems to be a particularly promising focus as suggested by the results thus far (Paivio & Bahr, 1998;Paivio & Patterson, 1999;Paivio & Nieuwenhuis, 2001;Smith, Pearce, Pringle, & Caplan, 1995). With the evidence of impaired interpersonal functioning in adult survivors of childhood sexual abuse (Elliott, 1994) and the demonstrated relationship between interpersonal variables and the development of a therapeutic bond (Paivio & Patterson, 1999), it seems that further investigation of these variables is in order.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Research on emotion-focused therapy (EFT) shows that interventions based on gestalt principles can achieve effects comparable to those of CBT interventions [16,17]. A review of 6 studies on the efficacy of experiential and gestalt-based treatments for traumatized patients [18] showed that there is a lack of methodologically rigorous research on gestalt-based therapies: the studies reviewed lacked either a control condition, a randomized design or failed to establish PTSD diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…It has a thorough theory of emotion and taxonomy of markers and a detailed worked-out set of tasks with well-defined steps. EFT is recognized as evidence-based treatment (APA, Div.12) for depression and for couple conflict, and there is empirical support for its effectiveness for trauma, interpersonal problems, and eating disorders (Elliott, Greenberg, & Lietaer, 2004;Paivio & Nieuwenhuis, 2001;Watson, Gordon, Stermac, Kalogerakos, & Steckley, 2003). EMDR also has a growing body of research on effectiveness in a wide range of disorders and is recognized as evidencebased treatment (American Psychiatric Association, 2004) for PTSD, and there is empirical support for its effectiveness for a variety of somatoform and anxiety disorders, as well as symptoms such as depression and anxiety resulting from sexual abuse (Edmond, Sloan, & McCarty, 2004).…”
Section: Resultsmentioning
confidence: 99%